1985
DOI: 10.1093/ajcn/42.5.753
|View full text |Cite
|
Sign up to set email alerts
|

The energy cost of common daily activities in African women: increased expenditure in pregnancy?

Abstract: We have performed, by open-circuit indirect calorimetry, a total of 1546 measurements of energy expenditure on 142 nonpregnant, pregnant, or lactating Gambian village women. Of the 47 common daily activities measured, only 7 would be classified as moderate according to internationally accepted standards, the remainder being light (ie requiring less than 3.5 kcal/min). This was unexpected since many of the tasks, judged subjectively, appeared quite demanding. Furthermore there was no increase towards the end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(24 citation statements)
references
References 17 publications
0
22
2
Order By: Relevance
“…RMR and its alterations induced by pregnancy have been documented elsewhere [1,5,10,17,18,20,[37][38][39][40][41] . Note that the RMR data presented in the relevant studies were not scaled but were adjusted for body weight using the simple ratio model which divides metabolic rate by weight.…”
Section: Discussionmentioning
confidence: 99%
“…RMR and its alterations induced by pregnancy have been documented elsewhere [1,5,10,17,18,20,[37][38][39][40][41] . Note that the RMR data presented in the relevant studies were not scaled but were adjusted for body weight using the simple ratio model which divides metabolic rate by weight.…”
Section: Discussionmentioning
confidence: 99%
“…The energy cost of DIT seems to be unaltered (Nagy and King, 1984;Poppitt et al, 1993;Spaaij et al, 1994;Bronstein et al, 1995;Piers et al, 1995;Prentice et al, 1996) or even reduced (Contaldo et al, 1987;Illingworth et al, 1987;KoppHoolihan et al, 1999). The energy cost attributed to PA is generally low (Lawrence and Whitehead, 1988;Butte et al, 2004;Clarke et al, 2005;Lof and Forsum, 2006;Rousham et al, 2006) and tends to decrease as pregnancy advances (Lawrence et al, 1985;van Raaij et al, 1987;Singh et al, 1989;Heini et al, 1991;Forsum et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that a major constraint preventing older women from spending more time grain processing is the energetic expenditure required. We calculated the amount of energy expenditure required for grain processing and mongongo nut processing from published sources (Lawrence et al 1985). Because we were unable to find measurements for energy expenditure for mongongo nut processing, we considered using measurements of energy expenditure for groundnut processing (1.41 kcal/min) and shellfish cracking (1.53 kcal/min) as proxies.…”
Section: Resultsmentioning
confidence: 99%
“…Grain processing is an energetically demanding activity; the estimate of 3.27 kcal/min. that we use places this activity as energetically equivalent to moderate exertion for the younger women and high moderate exertion for the older women (Lawrence et al 1985). Prior research in this community has shown that grain processing ability is largely based on strength and stamina while mongongo nut processing ability is largely based on experience (Bock 2005).…”
Section: Discussionmentioning
confidence: 99%